Modern use of geothermal energy in Nagyszénás (Case Study) - Szolga, Krisztián; Kocsis, Dénes (International Journal of Engineering and Management Sciences, 2022)
A project based on geothermal energy use in Nagyszénás, Békés County, Hungary, was finished on December 20, 2015. The construction investments were realized with the support of the European Union from tender funds won in the financial cycle of 2007-2013 in the total value of HUF 1.578 billion. The thermal water utilization investment was realized with unique technical solutions in the country, and as a result, a modern, economical heating system using green energy source was built, and now provides energy for the public institutions of the settlement and for the newly established bath complex. During construction and operation, several unforeseen technical problems arose, which could only be solved by using new technical elements. The high salinity and high temperature of the extracted thermal water required special engineering solutions. During operation, modifications and changes in technological elements were required at several points for the safe operation. The purpose of this article is to present these technical interventions, which made the reliable operation possible, thus the system provides a suitable alternative to natural gas-based heating.